2020
DOI: 10.1002/elan.202060285
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐based Potentiometric Biosensor for Monitoring Galactose in Whole Blood

Abstract: A filter paper sputtered with a layer of Pt and subsequently coated with a Nafion® membrane is used as working electrode. The mixed potential of the Pt electrode allows the detection of H2O2 generated by the oxidation of galactose in the presence of the galactose oxidase enzyme. This provides a simple and mediator‐free approach method. The system shows sensitivity values of −62.8±9.4 mV/decade of galactose in the range from 0.3 to 31.6 mM, well within the clinical relevant range. MnO2 nanoparticles were added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…49,50 However, numerous studies have revealed toxic corneal effects associated with BACs leading to unwanted effects such as destabilization of the tear film and death of the corneal and conjunctival epithelial cells. 51−53 To selectively detect BAC in diverse backgrounds, we incorporate an ionophore (calix [4]arene, C4X) into our sensing membrane. Results demonstrate that our BAC ISE responds in a Nernstian fashion (55.8 mV/Decade) to BAC + concentrations between 1.0 mM and 16.0 μM, which is comparable to a previous report using a PVC-BAC ISE (SI Table 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 However, numerous studies have revealed toxic corneal effects associated with BACs leading to unwanted effects such as destabilization of the tear film and death of the corneal and conjunctival epithelial cells. 51−53 To selectively detect BAC in diverse backgrounds, we incorporate an ionophore (calix [4]arene, C4X) into our sensing membrane. Results demonstrate that our BAC ISE responds in a Nernstian fashion (55.8 mV/Decade) to BAC + concentrations between 1.0 mM and 16.0 μM, which is comparable to a previous report using a PVC-BAC ISE (SI Table 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In fact, a steady increase in healthcare costs has been observed in many countries over the past 40 years, and the United States is no exception . This trend has motivated the scientific community to develop cost-efficient diagnostic tools that can be used in both laboratory and in-field (i.e., point-of-care, POC) settings. Potentiometry (i.e., the use of ion-selective electrodes, ISEs) is an ideal technique to exploit in developing POC sensors for the following reasons: (i) ISEs provide fast and reliable measurements. (ii) ISEs are selective for specific analytes in complex matrices (e.g., blood, urine, etc.…”
mentioning
confidence: 99%
“…Andrade’s research group described a paper-based potentiometric sensor for detecting galactose in whole blood . The authors used a filter paper sputtered with a layer of Pt and subsequently coated with a Nafion membrane as the indicating electrode.…”
Section: Miniaturized Ion-selective Electrodesmentioning
confidence: 99%
“…Andrade's research group described a paper-based potentiometric sensor for detecting galactose in whole blood. 175 The authors used a filter paper sputtered with a layer of Pt and subsequently coated with a Nafion membrane as the indicating electrode. For the reference electrode, a filter paper was first painted with a conductive Ag/AgCl ink and then covered with a PVB membrane doped with NaCl.…”
Section: Mittal Et Al Synthesized and Tested An Imine-based Ligand (E...mentioning
confidence: 99%
“…The researchers reported that aptamers have been mostly immobilized to gold and carbon-based electrodes via chemical cross-linking with particular attention to ensure biochemical stability, surface coverture and optimal binding affinity. Most common electrochemical techniques used for fabrication of biosensors are CV [76,77], EIS [78][79][80], potentiometry [81,82] and amperometry [83,84]. When real-time performance is required, time-based assays (such as chronoamperometry, chronocoulometry and chronopotentiometry) well fits medical applications.…”
Section: Electrochemical Transducingmentioning
confidence: 99%